Epigenetic and transcriptomic consequences of excess X‐chromosome material in 47, XXX syndrome—A comparison with Turner syndrome and 46, XX females. Issue 2 (3rd June 2020) - Nielsen, Morten Muhlig; Trolle, Christian; Vang, Søren; Hornshøj, Henrik; Skakkebæk, Anne; Hedegaard, Jakob; Nordentoft, Iver; Pedersen, Jakob Skou; Gravholt, Claus Højbjerg
Abstract: 47, XXX (triple X) and Turner syndrome (45, X) are sex chromosomal abnormalities with detrimental effects on health with increased mortality and morbidity. In karyotypical normal females, X‐chromosome inactivation balances gene expression between sexes and upregulation of the X chromosome in both sexes maintain stoichiometry with the autosomes. In 47, XXX and Turner syndrome a gene dosage imbalance may ensue from increased or decreased expression from the genes that escape X inactivation, as well as from incomplete X chromosome inactivation in 47, XXX. We aim to study genome‐wide DNA‐methylation and RNA‐expression changes can explain phenotypic traits in 47, XXX syndrome. We compare DNA‐methylation and RNA‐expression data derived from white blood cells of seven women with 47, XXX syndrome, with data from seven female controls, as well as with seven women with Turner syndrome (45, X). To address these questions, we explored genome‐wide DNA‐methylation and transcriptome data in blood from seven females with 47, XXX syndrome, seven females with Turner syndrome, and seven karyotypically normal females (46, XX). Based on promoter methylation, we describe a demethylation of six X‐chromosomal genes ( AMOT, HTR2C, IL1RAPL2, STAG2, TCEANC, ZNF673 ), increased methylation for GEMIN8, and four differentially methylated autosomal regions related to four genes ( SPEG, MUC4, SP6, and ZNF492 ). We illustrate how these changes seem compensated at the transcriptome level although several genes show differential exon usage. In conclusion, our results suggest an impact of the supernumerary X chromosome in 47, XXX syndrome on the methylation status of selected genes despite an overall comparable expression profile.